2018
DOI: 10.1016/j.ceb.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Body builder: from synthetic cells to engineered tissues

Abstract: It is estimated that 18 Americans die every day waiting for an organ donation. And even if a patient receives the organ that s/he needs, there is still >10% chance that the new organ will not work. The field of tissue engineering and regenerative medicine aims to actively use a patient's own cells, plus biomaterials and factors, to grow specific tissues for replacement or to restore normal functions of that organ, which would eliminate the need for donors and the risk of alloimmune rejection. In this review, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…6c-h). We and others have demonstrated that the cell-free secretome derived from stem cells can achieve a level of protection and regeneration similar or superior to the cells themselves 4,[26][27][28][29] . Our observations showed that LSC-Sec was capable of reversing fibrosis caused by Bleo or silica particles (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…6c-h). We and others have demonstrated that the cell-free secretome derived from stem cells can achieve a level of protection and regeneration similar or superior to the cells themselves 4,[26][27][28][29] . Our observations showed that LSC-Sec was capable of reversing fibrosis caused by Bleo or silica particles (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…Despite several advantages offered by in vitro/ ex vivo approaches, there are limitations to experimental reproducibility due to variations in human tissues/cells, obtaining tissues from individuals with underlying diseases, the limited availability of human tissues, and the interlaboratory differences in cell culture protocols, particularly involving 3D models [147]. With the incorporation of tissue printing technologies and the greater understanding of stem cell biology, the development of labgrown, standardized human tissues may not be too far in the future [157,158].…”
Section: In Vitro Modelsmentioning
confidence: 99%
“…A number of improvements and additions, based on previous cell delivery strategies, demonstrate better stem cell retention and promotion of endometrial repair after trauma . However, low retention and the propensity for tumorigenicity after administration still remain major obstacles for stem cell–based therapy …”
Section: Introductionmentioning
confidence: 99%